Mediating Role of Internet Self-Efficacy on the Relationship between Social Networking Sites’ Usage and Performance in Physics: Structural Equation Modeling Approach - Wasiu YAHAYA; Abdulrasaq Akanbi; Quadri Yahaya (International Journal of Advanced Humanities Research)
Social networking sites are online applications that were developed for communication and to have access to information. These sites can be accessed via phones, tabs, and other ICT gadgets through an internet connection. The study searched pre-service teachers’ usage of social networking sites and their relationship with their performance in physics with internet self-efficacy as the mediating variable. The study sampled three hundred and five (305) pre-service physics teachers across all teacher-producing colleges and universities in Kwara state, Nigeria using a convenient sampling technique. Adapted and researchers-designed instruments titled “Social Networking Sites Usage Questionnaire” which was divided into four sub-dimensions, “Physics Performance Test” and “Internet Self-Efficacy Scale” were used to elicit data from the respondents. A partial least square structural equation modeling approach was used and the data collected were analyzed via SmartPLS software version 4.0.9.2. The results of the study revealed that all four sub-dimensions of social networking sites’ usage were significantly related to student’s performance in physics. The study also found out that internet self-efficacy mediates the social networking site usage’s sub-dimensions relationship with students’ performance in physics significantly. The study concluded that proper usage of social networking sites aids students’ performance positively.